Benefit from extended surveillance interval on colorectal cancer risk in Lynch syndrome. (3rd February 2020) - Lindberg, L. J.; Rasmussen, M.; Andersen, K. K.; Nilbert, M.; Therkildsen, C.
Abstract: Aim: Although patients with Lynch syndrome have an increased risk of developing colorectal cancer, surveillance can reduce morbidity and mortality. Whether or not affected individuals benefit from lifetime surveillance depends on individual factors and patient adherence, and these may vary, complicating risk modelling. The aim of this study was to identify individual factors which influence patient adherence to surveillance programmes and whether extended surveillance interval influenced their risk of developing colorectal cancer. Method: Demographics and survival data were obtained from patients ( n  = 1223) with Lynch syndrome, identified by interrogating the Danish Hereditary Non‐Polyposis Colorectal Cancer Register. These data were linked to patient surveillance interval data which had been divided into three subsets (< 27 months, adherent to the recommended biennial programme; > 27 months, extended surveillance interval; and no surveillance) to estimate the cumulative risks and hazard ratios (HRs) for colorectal cancer. Results: In all, 147 colorectal cancers (99 first; 48 metachronous) were identified in 1223 patients. Factors associated with adherence to surveillance were female sex, a previous history of cancer and age < 75 years. The cumulative incidence for colorectal cancer was 38% (95% CI 27%–50%) for surveillance intervals < 27 months, 48% (95% CI 29%–67%) for intervals > 27 months and 72% (95% CI 61%–83%) with no surveillance. Adjusted HRs were 0.22 for surveillance intervals < 27 months and 0.32 for surveillance intervals > 27 months. Extended surveillance intervals > 27 months had a non‐significant benefit with an HR of 1.51 (95% CI 0.83–2.75) compared to surveillance intervals < 27 months. Conclusion: This study demonstrates that adherence to colonoscopic surveillance in Lynch syndrome varies with age, sex and cancer history and demonstrates a consistent benefit from colorectal cancer surveillance, though it might be lower for individuals with extended intervals.